Avaliação dos efeitos de Streptococcus mutans sobre formação de biofilme e morfogênese de Candida albicans in vitro e estudo experimental em Galleria mellonella - Barbosa, Júnia Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Interactions between fungi and bacteria are present in nature and has great medical and environmental importance. The development of adequate models in vitro and in vivo to characterize these interactions are essential for understanding the pathogenesis of diseases and discovery of new therapeutic strategies. The aim of this study was to evaluate the microbial interactions between Streptococcus mutans and Candida albicans in vitro and in an experimental model of Galleria mellonella. In the in vitro study, the effects of S. mutans on biofilm formation and on the filamentation ability by C. albicans were evaluated. On both tests, we evaluated the direct effects of S. mutans cells and indirect effects of the supernatant culture of S. mutans on C. albicans. Furthermore, the effects of the S. mutans were tested on C. albicans at different stages of growth of the bacterial culture (4, 6, 18 and 24 h). In vivo study, were inoculated S. mutans together with C. albicans in larvae of G. mellonella for induction of experimental infection. The effects of S. mutans on experimental candidiasis in G. mellonella was evaluated by analysis of the survival curve, the study of the culture of hemolymph for quantification of C. albicans and by histological evaluation the formation of hyphae of C. albicans in the host tissues. The results of in vitro tests and number of CFU/mL in G. mellonella were submitted to ANOVA and Tukey's test. The data obtained in the survival of G. mellonella were analyzed using the log- rank test. In all tests, were adopted significance level 5%. In vitro results showed that cells of S. mutans favored biofilm formation by C. albicans, however when C. albicans was put in contact with the only supernatant of a culture of S. mutans, there was a reduction in biofilm formation and inhibition of the morphological transition of C. albicans. In the in vivo study, it was found that the injection of ....

As interações entre fungos e bactérias estão presentes na natureza e tem grande importância médica e ambiental. O desenvolvimento adequado de modelos in vitro e in vivo para caracterizar essas interações é essencial para o entendimento da patogênese das doenças e descoberta de novas estratégias terapêuticas. O objetivo desse estudo foi avaliar as interações microbianas entre Streptococcus mutans e Candida albicans em modelos de biofilmes formados in vitro e em modelo experimental de Galleria mellonella. No estudo in vitro, foram avaliados os efeitos de S. mutans sobre a formação de biofilme por C. albicans e sobre a capacidade de filamentação de C. albicans. Em ambos os testes, foram avaliados os efeitos diretos das células de S. mutans sobre C. albicans e também os efeitos indiretos de S. mutans sobre C. albicans, utilizando apenas o sobrenadante da sua cultura. Além disso, foram testados os efeitos de S. mutans sobre C. albicans em diferentes fases de crescimento da cultura bacteriana (4, 6, 18 e 24 h). Para a realização do estudo in vivo, pela primeira vez na literatura, foram inoculados S. mutans juntamente com C. albicans em lagartas de G. mellonella para indução de infecção experimental. Os efeitos de S. mutans sobre a candidose experimental em G. mellonella foram avaliados pela análise da curva de sobrevivência, pelo estudo da cultura da hemolinfa para quantificação de C. albicans e através da avaliação histológica da presença de hifas de C. albicans nos tecidos do hospedeiro. Os resultados dos testes in vitro e da contagem de UFC/mL em G. mellonella foram submetidos à Análise de Variância e teste de Tukey. Os dados obtidos na curva de sobrevivência de G. mellonella foram analisados pelo método de Log-rank. Em todos os testes, foi considerado nível de significância de 5%. Os resultados in vitro demonstraram que as células de S. mutansfavoreceram a formação de biofilme por C. albicans ....
Keywords: Candida albicans; Streptococcus mutans; Biofilme